Visitor Perceptions of the 14th Makardhi Job Fair in 2023 at the Bali Tourism Polytechnic - Putu Adhe Rama Hendrawan; Indah Kusumarini; I Gede Sumadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The 14th Makardhi job fair at Bali Tourism Polytechnic aims to facilitate meetings between companies in the hospitality sector and job seekers. This study aims to evaluate visitor perceptions of the implementation of the 14th Makardhi job fair in 2023. The theory of six event dimensions by Silvers (2004) was used in this study, including anticipation, arrival, activity, atmosphere, appetite, and amenities. Data were collected through interviews, documentation studies, and questionnaires using the purposive sampling method to 102 respondents, and the data were tabulated, tested for validity and reliability, and processed using the Weight Mean Score method for each event dimension. The results showed that visitor perceptions of the 14th Makardhi job fair got an average score of 3.98 (Good). The highest value was obtained in the anticipation dimension with a value of 4.32 (Very Good), while the lowest values ​​were obtained in the atmosphere (3.64) and amenities (3.62) dimensions, which were included in the